Transformasi Kompetensi Guru di Era Digital: Tinjauan Terhadap Penguasaan Teknologi Informasi dan Komunikasi dalam Proses Pembelajaran - Dewi Angkat, Sri; Ludfi; Nelly (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2024)
This research aims to analyze the transformation of teacher competence in mastering information and communication technology (ICT) in the digital era, as well as the challenges and strategies faced in the learning process. The method used is a literature study with a qualitative-descriptive approach. Data was collected through searching indexed scientific sources from databases such as Google Scholar, JSTOR, ERIC and ProQuest which were selected based on relevance, novelty and source quality. The literature obtained was analyzed qualitatively using thematic content analysis. The research results show that the transformation of teacher competence includes increasing digital literacy, the ability to create interactive learning materials, and the use of digital platforms for teaching as an urgent need that requires a holistic response. Challenges faced include limited access to ICT infrastructure and the need to increase digital literacy and relevant pedagogical skills. Improving competencies should not only focus on technical training, but also strengthen pedagogical skills and adaptability. Support from the government, educational institutions and society is very important in creating an optimal learning ecosystem. Educational policies that support the development of ICT facilities and continuous training must be a priority, to ensure teachers and students can reach their maximum potential in the teaching and learning process in the digital era.